Dashboard IoT untuk Real-Time Monitoring Berbasis Node-RED dengan JSON dan Edge Computing pada Raspberry Pi - Luh Putu Ary Sri Tjahyanti; Putu Aditya Pratama; Putu Shantiawan Prabawa; Made Santo Gitakarma (JUKI : Jurnal Komputer dan Informatika, 2026)
The development of the Internet of Things (IoT) has enabled the implementation of real-time environmental monitoring systems in various sectors, including education. However, many schools still rely on manual facility monitoring, resulting in underutilized monitoring data. This study aims to develop and implement an IoT-based monitoring dashboard using Node-RED with JSON data exchange on a Raspberry Pi as an edge computing device to support real-time monitoring of school facilities at SMK Negeri 2 Seririt. The research adopts an applied research approach using a system engineering method that includes requirements analysis, system design, implementation, and system performance evaluation. The developed system utilizes Raspberry Pi as the edge device, Node-RED as the data integration platform, and a web-based dashboard for visualizing sensor data. The testing results show that the system achieves a data processing success rate of 98% with an average response time of 2.1 seconds, and reduces manual monitoring activities by approximately 35%. The contribution of this study lies in the development of an edge computing-based IoT monitoring dashboard and its direct implementation in a school environment, supporting data-driven smart school initiatives.